(untitled) (Research, Society and Development, 2022)
Objective: To compare the presence of pelvic organ prolapse (POP) and sexual dysfunction (DS) in primiparous adolescents who underwent vaginal delivery, according to exposure to episiotomy. Methods: A cross-sectional study was carried out at the Federal University of Pernambuco, with primiparous adolescents aged 10 to 19 years who gave birth 7 to 48 months before data collection. Participants filled out a form with their personal and clinical data and answered the International Incontinence Consultation Questionnaire on Urinary Short Form Incontinence, the Incontinence Severity Index and the Jorge & Wexner Incontinence Scale. Pelvic floor assessments were also performed. Statistical analysis was performed using SigmaPlot 12.0 and Statistical Package for the Social Sciences 25.0. Results: Our results showed a greater chance of functional alterations and the development of POP and SD in primiparous post-vaginal delivery adolescents who underwent episiotomy, compared to those who did not undergo an incision. Conclusion: Puerperal adolescents with functional alterations and pelvic floor dysfunctions should be referred for physical therapy treatment as soon as possible.